Peningkatan Kreativitas Anak Melalui Pendampingan Kegiatan Mewarnai Di TK Dharma Wanita 01 Prajegan - Nikmatulloh, Nizwatul; Ulfa, Risa Alfiyah; Mariana, Mariana (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Children's creativity needs to be increased with creative and innovative learning. One way to increase children's creativity is by painting and coloring activities. This research aims to increase children's creativity through coloring activities at Dharma Wanita 01 Prajegan Kindergarten. The method used in this research is ABCD research. Asset-Based Community Development (ABCD) is a model of community development approach. The subjects of this research were teachers and students of Dharma Wanita Kindergarten located in Dukuh Pacar, Prajegan Village, Sukorejo District, Ponorogo Regency, totaling 11 children. From the research conducted, it is clear that coloring activities carried out by young children can increase their creativity. Children can develop their imagination if they are given the freedom to explore their inner imagination. Educators and parents only need to accompany and direct, there is no need to limit children's movement. In this case, interesting and creative learning media are also needed that can arouse children's curiosity. Creative learning media can help children express and explore their imagination. This routine coloring activity is very useful for stimulating children's imagination and creativity in thinking, shaping their souls through emotional experiences and freedom of expression. The role of teachers and parents is important in accompanying the activities carried out by children, they can also provide rewards for the results obtained by children so that they can help foster children's enthusiasm and motivation for learning.